2020
DOI: 10.1186/s13104-019-4862-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of internet gaming disorder among secondary school students in rural community, Thailand: a cross-sectional study

Abstract: Objective: Internet gaming disorder (IGD) is an emerging mental problem for adolescent that has been increasingly piqued interest over the last decade. Although many studies have been conducted, very few studies have studied populations with low technological access. Therefore, this study aimed to estimate the prevalence and associated factors of internet gaming disorder among secondary school students in an area with a comparatively lower technological access in a large community sample. We used Chachoengsao … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
31
4
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 27 publications
(28 reference statements)
6
31
4
4
Order By: Relevance
“…While this may be the case, summary findings from two large reviews do have similar final estimates-5.5% [27] and 4.6% [28 •• ]. This rate is also similar to the prevalence of youth "at-risk" for IGD across Europe (5.1%) [29] and for full IGD in rural Thailand (5.4%) [35]. While far from definitive, 5% might be our strongest general prevalence estimate given the evidence.…”
Section: Prevalencesupporting
confidence: 70%
See 1 more Smart Citation
“…While this may be the case, summary findings from two large reviews do have similar final estimates-5.5% [27] and 4.6% [28 •• ]. This rate is also similar to the prevalence of youth "at-risk" for IGD across Europe (5.1%) [29] and for full IGD in rural Thailand (5.4%) [35]. While far from definitive, 5% might be our strongest general prevalence estimate given the evidence.…”
Section: Prevalencesupporting
confidence: 70%
“…Among middle and high school students in Japan, prevalence was 7.9% for problematic internet use and 15.9% for adaptive internet use, a lower cutoff of the diagnostic questionnaire [34]. In rural Thailand, 5.4% reached the cutoff for IGD [35], and in Taiwan 3.1% met that threshold [17]. Among 2666 urban middle school children in China, prevalence of IGD was 13.0% [36].…”
Section: Prevalencementioning
confidence: 94%
“…What is unique about the present study is that this relationship also extends to gaming disorder. This not only replicates previous studies reporting positive relationships between bullying victimization and PVG [52][53][54], yet provides evidence for the role of mental health symptoms in this relationship, accounting for 16.1% of the variance in PVG severity. The extent of the variance explained in this model points to the fact that various factors other than bullying victimization, externalizing and internalizing problems may explain youth PVG, including self-esteem, impulsivity, attention difficulties, social competencies and parental relationship quality [16].…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, some studies have found that frequent video game playing has been associated with increases in cyberbullying perpetration (or of being both a victim and perpetrator of bullying [i.e., bully-victims]), within and outside online gaming environments [43][44][45][48][49][50][51]. Specific to PVG, direct positive relationships have been identified between bullying victimization and PVG [52][53][54]. However, little research has investigated the potential mediators explaining the relationship between these variables.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, other studies reveal the prevalence of IGDs varies in the range between 1%-9% depending on the age of the respondent, country, and other sample characteristics (Gentile et al, 2017). The prevalence of IGD for rural adolescents living in a province in Thailand in 2018 was 5.4% (Taechoyotin, Tongrod, Thaweerungruangkul, & Towattananon, 2020). The prevalence of online game addiction in Indonesia has not been well documented.…”
Section: Introductionmentioning
confidence: 99%